2008
DOI: 10.1109/tro.2008.915445
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Natural Language Interface for Transferring Grasping Skills to Robots

Abstract: In Sections III-VI, admittance selection conditions for four typical two-PC states each in single-point contact were presented. The strategies and procedures can be used for any combination of two single-contact PCs. In general, for each PC, translational variables δ ij are chosen based on the PC's type. Using translational variables δ ij and orientational variables (u, θ), the contact wrenches w i and errormeasure vector d are obtained and the interaction of the wrenches from the two PCs is addressed in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In 3.7% of papers (n = 2), authors reported having the Wizard perform manipulation tasks. Ralph and Moussa (2008) describe a task where the Wizard takes both user's commands and the robot's limitations into account when selecting commands for it; Robins et al (2008) describe a Wizard controlling a 3-DOF drumming robot.…”
Section: Nonverbal Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…In 3.7% of papers (n = 2), authors reported having the Wizard perform manipulation tasks. Ralph and Moussa (2008) describe a task where the Wizard takes both user's commands and the robot's limitations into account when selecting commands for it; Robins et al (2008) describe a Wizard controlling a 3-DOF drumming robot.…”
Section: Nonverbal Behaviormentioning
confidence: 99%
“…Only 5.4% of included papers (n = 3) described providing the Wizard training. Ralph and Moussa (2008) provided their Wizard two months of training prior to beginning their experiment, to ensure that the Wizard "did not influence each participant's choice of language or commands used during the study. "…”
Section: Constrainedmentioning
confidence: 99%
“…The apparent limitation of such methods is that they assume the presence of an expert for reprogramming, which makes them unsuitable for the envisioned transformable factories. In contrast to the majority of publish works and similar to our approach, the authors of [36] combined skill primitives and speech recognition for programming grasping tasks by speech, with other work presented in [37,38]. This work incorporates task-level programming, however, the programming is a combination of primitives, with no higher-level skills between these and the task layer.…”
Section: Related Workmentioning
confidence: 99%
“…Such a system would need to perform tasks like fine-grained pose estimation and grasp planning. For example, the user could interact with the system to correct its mistakes, or instruct it to use certain grasping techniques for certain objects; see for example Ralph and Moussa (2008). We also envision extending our approach to use 3D point cloud data to match objects to extensive online computer aided design model databases.…”
Section: Future Workmentioning
confidence: 99%